2021
DOI: 10.1177/0271678x211012110
|View full text |Cite
|
Sign up to set email alerts
|

CSF lipocalin-2 increases early in subarachnoid hemorrhage are associated with neuroinflammation and unfavorable outcome

Abstract: Lipocalin-2 mediates neuro-inflammation and iron homeostasis in vascular injuries of the central nervous system (CNS) and is upregulated in extra-CNS systemic inflammation. We postulate that cerebrospinal fluid (CSF) and blood lipocalin-2 levels are associated with markers of inflammation and functional outcome in subarachnoid hemorrhage (SAH). We prospectively enrolled 67 SAH subjects, serially measured CSF and plasma lipocalin-2, matrix metallopeptidase 9 (MMP-9), interleukin-6 (IL-6) and tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The pathological mechanisms of EBI include oxidative stress, platelet activation, inflammation, and neuronal apoptosis 41–46 . Additionally, new studies showed that microthrombi formation, vascular injury and iron homeostasis disorder were also important mechanisms of EBI after SAH 47,48 . One animal experiment found that hyperglycemia could increase reactive oxygen species (ROS) production through activating protein kinase C after stroke, thereby exacerbating oxidative stress 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological mechanisms of EBI include oxidative stress, platelet activation, inflammation, and neuronal apoptosis 41–46 . Additionally, new studies showed that microthrombi formation, vascular injury and iron homeostasis disorder were also important mechanisms of EBI after SAH 47,48 . One animal experiment found that hyperglycemia could increase reactive oxygen species (ROS) production through activating protein kinase C after stroke, thereby exacerbating oxidative stress 49 .…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46] Additionally, new studies showed that microthrombi formation, vascular injury and iron homeostasis disorder were also important mechanisms of EBI after SAH. 47,48 One animal experiment found that hyperglycemia could increase reactive oxygen species (ROS) production through activating protein kinase C after stroke, thereby exacerbating oxidative stress. 49 In another study, hyperglycemia aggravated neuronal apoptosis through the activation of extrinsic caspase cascade via extracellular regulated kinase (ERK) signal pathway after experimental SAH.…”
Section: Variablementioning
confidence: 99%
“…LCN2 is also upregulated in serum and liver tissue of patients with non-alcoholic fatty liver (NAFL), and serum LCN2 levels could be a novel biomarker for the diagnosis of non-alcoholic steatohepatitis (NASH), which may be participate in the transition from NAFL to NASH by mediating inflammation. Besides, LCN2 has been demonstrated as a biomarker for inflammatory bowel disease ( Thorsvik et al, 2017 ), vascular dementia ( Llorens et al, 2020 ), neuropsychiatric lupus ( Mike et al, 2019 ), and subarachnoid hemorrhage outcome ( Yu et al, 2021 ). The level of LCN2 could predict disease severity and survival in acute kidney injury ( Bennett et al, 2008 ; Kümpers et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…One is haemolytic product-induced secondary neuroinflammatory factors, such as inflammasome-derived caspase-1 activity, which is tightly associated with blood coagulation in CSF and poor prognosis of SAH patients. 6 Elevated CSF lipocalin-2 mediates neuroinflammation and iron homeostasis and is reported to be a biomarker for unfavourable outcomes of SAH patients 7 and a potential therapeutic target for long-term neurological rehabilitation. 8 …”
Section: Intersections In the Pathophysiological Changes Induced By T...mentioning
confidence: 99%